Community-based Economic Development and Partnership Cooperation: The Economics Strategy for Prosperity of the Ummah - Ali, AM Hasan (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The term welfare of the people is still an interesting study to imagine. Prosperity in Indonesia is still not evenly distributed, it can only be enjoyed by some of the Indonesian population. Muslims constitute the majority of Indonesia's population, including those who have not experienced prosperity. Identification of economic problems as the cause of not achieving the welfare goals of Muslims, among others, caused by poverty, unequal income and poverty. Responding to these problems, there is a need for an economic strategy to realize people's welfare. This study uses a normative legal method using a community empowerment theory approach. Research data is based on literature studies which refer to journal articles, books and scientific sources related to the focus of discussion. This research concludes that in the context of zakat management, there are several strategies that need to be carried out in the context of community empowerment, including optimizing the management of sharia social funds sourced from alms (zakat), donations (infaq), alms (sadakah), and waqf (ziswaf) as well as welfare empowerment. Community economy through mosque management. This study also argues that for economic strategy options to achieve the prosperity of Islamic communities, first, expand the scope of partnerships between capital owners and managers, including providing profit sharing cooperation options for acquiring affected land; Second, community-based economic development, such as in the NU and Muhammadiyah communities, is supported by the development of application systems to build markets within the NU and Muhammadiyah communities. Third, expanding literacy and access to entrepreneurship among Indonesian Muslims, including by providing mandatory entrepreneurship courses as national mandatory subjects.